FAO economic and social development paper N.136: Growth theories, old and new and the role of agriculture in economic development - Nicolas Stern (FAO, 1995)
The question addressed by the author in thisc study is: What assessment can be made of the insights from the new theories of growth for the understanding of the role of agriculture in economic development? The answer provided may appear surprising and bold. The claim is that agricultural economic literature had for long emphasised the importance of cumulable factors such as research, education and extension that are specific instances of the human capital and technological advance that dominate endogenous growth theory.